Tourism web services using e-business - Muchlis, Esa Firmansyah (2008)
E-tourism is a leading area in e-commerce, with an increasing number of travel agencies offering their services through online transaction brokers. This project started with requirements-gathering activities based on the questionnaires given to travel agencies and customers. We conducted the literature review on tourism sector that support with different technology. The purpose is to understand what really needed by the travel agencies in order to improve their business and propose a value added to their customer services. Mobile reservation is needed for travelers who usually move from one place to another, providing this mobile reservation system can help them to plan their businesses or holiday trips. Mobile reservation is also needed for travel agent and service provider to support their services. This project describes the development of mobile application that can invoke services from airline, car rental, to hotel reservation through travel agent as a broker. The implementation of web service technology and service-oriented architecture based on loose coupling principle among interacted-system has been used in developing this project. In the end of the project, some questionnaires regarding to the testing and satisfaction level of users have indicated the applicability of the proposed approach.